Students' Critical Thinking Skills In Solving Hots-Oriented Numeracy Problems - Putri Nur Habibah; Christina Kartika Sari (Universitas Wiralodra, 2025)
Critical thinking skills are the expected outcome of the student learning process and are a means to support student growth and development. This study aims to present the results of the analysis of the critical thinking ability process of grade X students with high, medium, and low initial abilities in solving HOTS-oriented numeracy problems on the Three-Variable Linear Equation System material and to determine students' critical thinking abilities in each critical thinking indicator. HOTS-oriented numeracy problems are numeracy problems designed to develop students' high-level thinking skills. These questions require students to analyze, evaluate, and create solutions based on deep understanding. The type of research used in this study is qualitative research with a descriptive approach. The subjects of this study were six students with varying initial abilities. Sampling in this study used random samling technique. Data collection techniques were carried out through tests, interviews, and documentation. The results and conclusions of this study showed a relationship between student abilities and the level of critical thinking indicators. Students with high initial abilities tend to be able to meet all critical thinking indicators, while students with moderate and low initial abilities experience various obstacles in several aspects.